Optical Absorption Bands in the Milled Gallium Oxide-hematite Nanoparticles System - Sorescu, Monica; Kelly, Jordan; Aitken, Jennifer (Transactions on Engineering and Computing Sciences, 2025)
Nanoparticles of the gallium oxide-hematite mixed-oxide system were synthesized by mechanochemical activation using high-energy ball milling for durations of 0, 2, 4, 8, and 12 hours. Optical diffuse reflectance spectroscopy (ODRS) measurements were performed across the full UV-VIS-NIR range. Optical absorption bands in the spectra of hematite and gallium oxide nanoparticles were identified. Hematite (Fe2O3) exhibits a strong absorption band in the visible range (~2.2 eV), while other prominent absorption bands are located at ~3.1-3.2 eV and ~5.3-5.8 eV. These features arise from the electronic structure of the iron ions and the crystal lattice, with antiferromagnetic interactions in certain structural configurations enhancing the intensity of the absorption bands. Ga2O3 has an intrinsic bandgap of approximately 4.8 eV, rendering it transparent throughout the visible and into the deep-UV region. Free electrons in doped Ga2O3 can absorb light from the IR to UV via transitions between conduction bands, including a direct optical transition that occurs at approximately 3.55 eV (349 nm). The optical absorption properties of the gallium oxide-hematite system were found to depend on the milling processing parameters.